Peningkatan Keaktifan Belajar dan Hasil Belajar Siswa Melalui Model Pembelajaran Numbered Head Together dengan Media Mind Mapping Pada Mata Pelajaran Ekonomi Kelas X IPS 1 SMA Negeri 1 Kerinci - Eka Apriya Dewi (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This research was a classroom action research. It was figure out that during the learning and teaching process the student’s activeness and achievement were still low. Therefore, this resarch was conducted to solve the problem by implementing Cooperative Number Head Together by using Mind Mapping media. The rersearch participant was the students at grade X IPS 1 of SMAN 1 Kerinci. The objective of the reserasch was to improve the student’s comprehension on economics concept and activeness during the learning and teaching process. The collaborator of the research was the teacher who taught the same subject. The study was conducted in two cycles consisted of four stages;(a) planning, (b)action, (c) observation (d) reflection. The analysis result showed that there was significant improvement on the student’s achievement and activeness after Cooperative Number Head Together by using Mind Mapping Media was applied. The student’s average score in Pre cycle was 50 (42%). Then, in cycle 1 the score was 71 (67%), in cycle 2 it improved significantly to 78 (76%). In addition, the student’s activeness in cycle 1 was 65,55%, and in the second cycle it improved to 79,36%. Based on the data, it concluded that the implementation of Cooperative Number Head together by using Mind Mapping Media improved the student’s achievement and activeness significantly. Therefore, it was suggested to Economic Teacher to apply the method as the alternative solution to the student’s learning problem especially on Economic Agent Subject.